Kimura disease: A rare cause of painless lymphadenopathy in South Asia - Prabhat Rijal; Madhav Banjade; Nirmal Kumar; Rohit Raina; Monika Pathania; Ravi Kant (Journal of Family Medicine and Primary Care)
Kimura disease is an uncommon disease entity that typically involves the lymph nodes predominantly in the head and neck region together with frequent involvement of salivary glands. Very few cases of it have been reported in literature globally, and in the context of India, it is even rare. Early suspicion of Kimura disease may prevent the patient from unnecessary invasive diagnostic tests. We present a case scenario of a 35 years old female, from a hilly area who presented with painless neck swelling for 3 months that was followed by fever, new onset pain at the site of neck swelling, and skin rashes. Diagnosis of Kimura disease was made based on histopathological findings aided by peripheral eosinophilia and elevated serum Immunoglobulin E (IgE) levels. Following the diagnosis, the patient was treated with a short course of oral steroids which produced an excellent response with a consequent decrease in the size of lymph nodes and resolution of the skin rashes.